Trade Liberalisation and Global-scale Forest Transition - Rafael González-Val; Fernando Pueyo (Fondazione Eni Enrico Mattei (FEEM), 2013)
In this paper, we develop a theoretical model that provides an additional explanation for the forest transition based on a trade liberalisation scenario. Furthermore, in contrast with most explanations, in which the forest transition can only take place at a local level at the expense of other areas, ours is capable of supporting such phenomenon at a worldwide level. We introduce a renewable natural resource (wood), used as an input by manufacturing firms, in a framework with economic geography foundations: transport costs affect the distribution of firms between countries. In a general equilibrium, the results reproduce the forest transition at a global scale: a decrease in transport costs (in particular, that of the natural resource) has a negative effect on the worldwide stock of the natural resource in the short-term; however, this effect is offset during the transition as a consequence of industrial reallocation between countries and eventually disappears in the long-run.
Keywords: F18; Q20; Q23; R12; 330; Forest Transition; Natural Resources; Industrial Location; Trade Liberalisation